Kecurangan Akademik dalam Moda Pembelajaran Digital di Perguruan Tinggi - Ainul Yaqin; Suadi Suadi (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
Education actually has the task of forming the character of students, one of which is honest character. However, the educational process itself sometimes provides opportunities for students to deviate from honest character, for example the facilities for academic cheating in online learning are provided. This research is aimed at exploring forms of academic cheating in digital learning and their causes, and efforts to overcome them from the perspective of students. This type of qualitative research was deliberately chosen because it has adequate tools to be able to explore data in detail and depth. Data collection uses observation, interviews and documentation studies. The results of the study concluded that the prominent mode of academic cheating was taking material from the internet without using scientific principles (plagiarism) and copying the work of friends to send as their work (cheating). The cause of academic cheating occurs is the ease of access to material from digital technology without an adequate academic cheating prevention system and the mentality or character factors of students. Various techniques to deal with academic cheating include; strengthening character formation, giving strict punihsment, and changing assignments or exams to be individualistic by emphasizing meaningful analytical skills.